(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Background: The intersecting clinicopathological features and histological patterns, including cribriform, tubular and solid patterns of adenoid cystic carcinoma (ACC) and polymorphous low-grade adenocarcinoma (PLGA) may end in a problematic diagnosis .ACC has a worse prognosis than PLGA making distinction important for therapeutic and prognostic purposes . The Aims of this study were to evaluate the immunohistochemical expression of CD105 and Ki-67 in adenoid cystic carcinoma and polymorphous low grade adeoncarcinoma of the salivary glands and to correlate the immunoexpression of these proteins with the clinicopathological findings. Materials and methods In this retrospective study , fifty of archival formalin fixed paraffin embedded tissue samples of salivary gland malignancies were used, twenty five blocks of adenoid cystic carcinomas and twenty five blocks of polymorphous low grade adenocarcinoma obtained from the archives of the department of oral pathology / college of dentistry / Baghdad university, Al-Shaheed Ghazi hospital, were included in our study. Four micrometer sections gained and immunostained using monoclonal antibody against CD105 and Ki-67. The immunoexpression was identified by the presence of brown stain in the cytoplasm of tumor cell in CD105 and the presence of brown stain in the nucleus of tumor cell in Ki-67. The proportion of cells that expressed the stain was correlated with the clinicopathological data of the patients. Results: CD105 expression was found positive in 21 cases of ACC and 20cases of PLGA localized in tumor cells. andKi-67 expression was found positive in 24 cases of ACC and 23 casesof PLGA localized in tumor cells. Non- significant statistical relation (P=0.801) was detected regarding CD105 expression in both types of tumor and non- significant statistical relation (P= 0.852) was detected regarding Ki-67 expression in both types of tumor . Non- significant statistical relation (P= 0.05) was detected regarding CD105 and Ki-67 expression in relation to sex, site and stage in both types of tumor. Conclusion: Weak expression CD105 and Ki-67 in ACC and PLGA might be explained by CD105 and Ki-67 did not represent an exclusive factors consequently; other factors might be involved in the proliferation, progression and metastasis of both tumor types. Key words: Adenoid cystic carcinoma, Polymorphous low grade adenocarcinoma , immunohistochemistry, CD105 and Ki-67.